Distribution of linear alkylbenzenes (LABs) in sediments of Sarawak and Sembulan Rivers, Malaysia - Magam, Sami Muhsen; Zakaria, Mohamad Pauzi; Halimoon, Normala; Masood, Najat; Alsalahi, Murad Ali (Thai Society of Higher Education Institutes on Environment, 2012)
The current study is one of the first studies evaluating the levels of linear alkylbenzenes (LABs) in surface sediments of Sarawak and Sembulan rivers which are located in the east coast of Malaysia. The LABs, which are molecular tracers of sewage contamination, were measured in 15 surface sediment samples collected from these rivers. The samples were extracted, fractioned and analyzed by gas chromatography mass spectrometry (GC-MS). The findings revealed that the concentrations of ΣLABs ranged from 156.47 to 7386.19 ng/g dry weight (dw) in the sediments of Sarawak River and from 643.18 to 5567.12 ng/g dw in the sediments of Sembulan River. The highest LABs levels were detected in the sediments collected from the sampling location SS9 in Sembulan River whereas the lowest levels were observed in the SS1 sampling location in Sarawak River. The I/E ratios(ratio of internal to external isomers of LABs) for Sarawak River sediments ranged from 0.52 to 0.98 while for Sembulan River they fell within the range 0.87-1.79. The I/E ratio at the sampling station SS4 was much lower than the I/E ratios at the other stations, thus indicating that the wastewater discharged into Sarawak River from the areas surrounding station SS4 was poorly treated.